Development Pattern on Lymph Node Resection in Minimally Invasive Esophagectomy and 2-year Survival Analysis - Zhao, Yunpeng; Dong, Xiaopeng; Cong, Bo; Peng, Chuanliang; Sun, Qifeng; Hao, Yingtao; Zhao, Xiaogang (The Thoracic and Cardiovascular Surgeon, 2016)
Background Thoracoscopic-laparoscopic procedures have been used more in the operations of esophagus cancer; in most times we call it minimally invasive esophagectomy, which is becoming mature. However, the efficacy of minimally invasive esophagectomy is still unclear, especially about the dissection of lymph nodes and survival.Methods A retrospective review was performed. The development process of minimally invasive esophagectomy for esophageal cancer was divided into three stages: the first stage 20, the second stage 37, the third stage 50.Result Total 107 patients underwent minimally invasive esophagectomy between July 2010 and May 2015. The number of lymph node resected during the three stages increased significantly, with a mean of 12.65, 15.91, and 20.16 nodes, respectively (p = 0.0075). The number of lymph nodes dissection greater than or equal to 12 or 18 increased significantly (p = 0.000). The patients from the first and the second stages had the similar 2-year survival rate (p = 0.8618). There is no significant difference in the 2-year disease-free survival rate (p = 0.606).Conclusion Surgeons accumulate experience on lymphadenectomy during minimally invasive esophagectomy as time goes by, and experience on 50 to 60 cases is essential and necessary to accomplish an apparent progress.
Keywords: minimally invasive esophagectomy; esophageal cancer; lymph node; survival analysis